2015
DOI: 10.1111/ppa.12406
|View full text |Cite
|
Sign up to set email alerts
|

Phakopsora myrtacearum sp. nov., a newly described rust (Pucciniales) on eucalypts in eastern and southern Africa

Abstract: Outbreaks of a rust disease in eucalypt forestry plantations and nurseries in Kenya, Mozambique and South Africa occurred between 2009 and 2014. The pathogen was identified using morphology and molecular phylogenetic analyses as an undescribed species in the Phakopsoraceae. A systematic study, based on nuclear ribosomal DNA, showed that it is a species of Phakopsora, herein named Phakopsora myrtacearum sp. nov. This new species of rust is the second validly described species on Eucalyptus, along with Puccinia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The present study recovered P. psidii sister to Dasyspora within the Sphaerophragmiaceae, sister to the Pucciniaceae, a relationship that was previously shown by Maier et al (2015) and Beenken and Wood (2015). Puccinioid spores are a homoplasious character within the Pucciniales (Beenken and Wood 2015).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The present study recovered P. psidii sister to Dasyspora within the Sphaerophragmiaceae, sister to the Pucciniaceae, a relationship that was previously shown by Maier et al (2015) and Beenken and Wood (2015). Puccinioid spores are a homoplasious character within the Pucciniales (Beenken and Wood 2015).…”
Section: Discussionmentioning
confidence: 76%
“…New disease reports from countries with susceptible hosts are eliminated as potential sources, as the rust would be expected to occur there already. Previous studies have indicated that the origin of P. psidii may be from a location with shared plants in the Annonaceae and Myrtaceae (Maier et al 2015)..…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations